Features of measles diagnostics and prevention at the present stage - Ya. M. Eremoshkina; T. K. Kuskova; E. T. Vdovina; A. V. Savina; M. V. Bogdanova; S. I. Kotiv (Лечащий Врач)
Considering the world health organization’s strategic plans to combat measles, there is an urgent need for early diagnostics and prevention of the disease. Taking into account the growing incidence of measles in the Russian Federation and in the world as a whole, there is a need to develop clear criteria for the diagnostics of measles. The algorithm for diagnosing measles, presented in this article, allows to suspect this disease at the early stages. This allows timely isolation and, if necessary, hospitalization of patients with measles.